Mamnu’ min al Sharf (Diptotes) in the Book al Mawa’idz al ‘Ushfuriyyah (Morphosyntax Analysis) - Mohamad Yusuf Ahmad Hasyim; Ahmad Zaenudin; Muhammad Danial Fahmi; Mudrofin Mudrofin; Kamaluddin Kamaluddin; Muhammad Azam (Lughawiyah: Journal of Arabic Education and Linguistics, 2025)
This study aims to know the types, patterns, cases and grammatical markers, and syntactic functions of mamnu’ min al sharf in the book al Mawa’idz al ‘Ushfuriyyah. This research employs a descriptive method with a library research design. The data were taken from the book al Mawa’idz al ‘Ushfuriyyah using reading and writing technique, with the researchers serving as the main research instrument. The results of this study show: based on types and patterns, there are eight types of mamnu’ min al sharf with varied patterns. Based on cases and grammatical markers, there are 21 nominative case data (marked with the vowel sound suffix /u/ and vowel sound suffix /u/ supposed), 7 accusative case data (marked with the vowel sound suffix /a/ and vowel sound suffix /a/ supposed), 31 genitive case data (marked with the vowel sound suffix /a/ and vowel sound suffix /a/ supposed), and 1 permanent datum in accusative case slot (marked with permanent with the vowel sound suffix /u/). Based on syntactic functions, there are data having syntactic functions such as topic, comment, agent, pro-agent, comment of indeed, noun of to be, object, comment of to be, noun of indeed, vocative noun, genitive case noun, genitive complement, conjunct, and attributive adjective. This study examines mamnu’ min al-sharf in Al-Mawa‘idz al-‘Ushfuriyyah to identify its types, patterns, cases and grammatical markers, and syntactic functions. The findings contribute to Arabic grammatical studies and practically support Arabic language teaching by clarifying the contextual use of mamnu’ min al-sharf.